Detection and characterization at nM concentration of oligomers formed by hIAPP, Aβ(1–40) and their equimolar mixture using SERS and MD simulations. Issue 31 (30th July 2018) - D'Urso, Luisa; Condorelli, Marcello; Puglisi, Orazio; Tempra, Carmelo; Lolicato, Fabio; Compagnini, Giuseppe; La Rosa, Carmelo
Abstract : We report a structural investigation on IAPP, Aβ(1–40) and their equimolar mixture at nM concentration using SERS spectroscopy and molecular dynamic simulations. Abstract : We report a structural investigation on IAPP, Aβ(1–40) and their equi-molar mixture aggregation pathway at nano-molar concentration using the Surface Enhanced Raman Spectroscopy (SERS) effect induced by silver metal colloids prepared by laser processes in solution and molecular dynamics simulations. Our data show the ability of silver NPs coupled with SERS to detect secondary structures of IAPP, Aβ(1–40) and their 1 : 1 molar ratio mixture in the oligomeric state. The preparation of silver colloids shows superior performance with respect to chemically prepared nano-particles. SERS spectroscopy shows both selectivity and sensitivity in detecting the secondary structures of hIAPP and Aβ(1–40) and to recognize both proteins in their mixture. On the other hand, molecular dynamics simulations confirm SERS structural data and the given atomistic details about the structural organization of IAPP and Aβ(1–40) oligomers. Our study shows an inhomogeneity in the chemical composition of IAPP/Aβ(1–40) oligomer aggregates.